THE USE OF VIDEO IN TEACHING SPEAKING - Maulana, Cepri (2016)
The research was aimed to explain the use of video provides support for junior high school students in speaking English and the students' responses to the use of video in teaching speaking activities for junior high school students. The qualitative method was conveyed in order to collect the data with observation and interview as the instruments of the research. The results showed that video provides some support for students in speaking English, which are 1) video becomes a source of information 2) video provides picture and sound 3) video creates fun and exciting teaching environment 4) video activates students' enthusiasm 5) video stimulates students' confidence. The result also revealed there was a positive response of students toward the use of video in teaching speaking.